2020
DOI: 10.1097/sap.0000000000002103
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Reconstruction After Colorectal Cancer Resection

Abstract: Background Colorectal cancer is one of the most common and fatal malignancies in the United States. When localized to the distal gastrointestinal tract, surgical therapy includes abdominoperineal resection (APR) or pelvic exenteration (PEX). Subsequent ablative defects are considerable, impart concerning morbidity, and often necessitate autologous reconstruction. The aim of this study was to assess postoperative outcomes after reconstruction of APR and PEX defects. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…For instance, a larger series on ablative surgeries described smoking as an independent risk factor for complications. 26 Analysis of more cases in the future might clarify the impact of smoking on healing time and incidence of complications.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a larger series on ablative surgeries described smoking as an independent risk factor for complications. 26 Analysis of more cases in the future might clarify the impact of smoking on healing time and incidence of complications.…”
Section: Discussionmentioning
confidence: 99%
“…1 The 5-factor modified frailty index (mFI-5) is a validated tool to assess frailty in preoperative patients and has been proven to be a good indicator of postoperative complications mortality and a fair indicator of 30-day hospital readmissions. This has been validated in multiple specialties such as general and orthopedic surgery [2][3][4][5] ; however, in the plastic surgery literature, there have been no studies that have looked at the association of mFI-5 with complications after breast reconstruction.…”
mentioning
confidence: 99%
“…Even though the superiority of each method with regard to wound healing complications remains controversial in the literature, most studies demonstrate that attempts at primary closure following abdominoperineal resection are associated with high morbidity and complication rates. [1][2][3][4][5][6][7][8][9][10][11][12][13] Immediate flap reconstruction following abdominoperineal resection reduces the incidence of wound healing complications and fills dead-space created by tumor extirpation. 1,[4][5][6][7][8][9][10]12 More specifically, immediate flap reconstruction has been associated with lower rates of local…”
mentioning
confidence: 99%
“…3,5,[7][8][9][10] Extant literature has focused on investigating patient outcomes after primary closure compared to flap reconstruction and identifying subsets of patients who benefit more from immediate flap reconstruction following abdominoperineal resection. [1][2][3][4][5][6][7][8][9][10][11][12][13] Other investigations have compared patient outcomes with different types of soft-tissue flaps in autologous reconstruction, with most studies demonstrating better outcomes with vertical rectus abdominis muscle flaps. [14][15][16][17][18][19][20][21][22][23][24][25][26] In a recent population-based analysis published by Billig et al, effective cost and resource use postoperatively at 6 months were found to be similar between patients who underwent abdominoperineal resection with immediate flap reconstruction in comparison to patients who underwent abdominoperineal resection alone, further supporting the utility of flap reconstruction after abdominoperineal resection in select patients and demonstrating that flap reconstruction is a judicious use of health care resources.…”
mentioning
confidence: 99%
See 1 more Smart Citation